ANALISISSISTEMINFORMASIAKUNTANSI PENGENDALIAN BAHAN BAKU DALAM MENINGKATKAN EFEKTIFITAS DAN EFISIENSI PADA PT XYZ - Safri, Safri (Universitas Dirgantara Marsekal Suryadarma, 2017)
The company goal is to maximize the value of the company and its normative can be realized by maximizing profit, which profitability is sales minus the cost of goods and reduced again with loads running, On the most important element of a business unit is supply, so the control of the company is a fixed price that must be achieved and ways to achieve it can be done effectively and efficiently. Analysis Information System of Accounting at the operational running needs to be done in order to achieve effective and efficient, PT XYZ as a manufacturing company is already implementing a system of accounting information on the application of inventory control, but the process is running, there are still obstacles that occur so that the effectiveness and efficiency there are still gaps for reconsideration. Still there is input data manually and documenting data that could lead to data loss. Review the information system running is expected to make the company more effective and more efficient in the future.